Proceso de ASC - CONCEPCION, DISEÑO Y DESARROLLO DE JUEGOS EDUCATIVOS PARA LA ENSEÑANZA DEL EMPRENDIMIENTO (2019)
The purpose of the project is to develop an educational game that facilitates the teaching of concepts and the strengthening of entrepreneurial skills in university students, aiming to provide more experiential teaching-learning processes that engage students through active learning methodologies. This will enable the university to achieve its objectives of teaching, research, and outreach.